STRATEGIC MANAGEMENT OF ACADEMIC HUMAN CAPITAL AS A DRIVER OF HIGHER EDUCATION INSTITUTION COMPETITIVENESS IN UZBEKISTAN (World Economics and Finance Bulletin, 2026)
The competitiveness of higher education institutions is increasingly determined by the ability to transform academic staff capacity into measurable teaching, research, innovation and internationalization outcomes. This article examines academic human capital not simply as a personnel resource, but as a strategic institutional capability that links university governance, quality assurance, digital transformation and labor-market relevance. The study is based on a qualitative analytical design that synthesizes human capital theory, the resource-based and dynamic capability views, international university ranking methodologies, official statistics on higher education in Uzbekistan and national policy priorities until 2030. The article argues that the rapid expansion of access in Uzbekistan has created a new management challenge: universities must move from quantitative growth to quality-based competitive differentiation. The proposed Academic Human Capital Strategic Management Framework integrates six mutually connected functions: attracting talent, developing competencies, motivating performance, connecting with industry, digitalizing academic work and measuring institutional results. The findings show that sustainable competitiveness requires not occasional professional training, but a continuous human capital architecture supported by data dashboards, transparent career pathways, research mentoring, international collaboration and outcome-oriented incentives.
Keywords: academic human capital; higher education competitiveness; faculty development